Psychological Degradation of the Main Character in the Novel “The Executioner’s Song” by Norman Mailer - Elmira Muratova; Mukhlisa Khidirova (Genius Journals, 2022)
The article deals with psychological problems of the main character of Norman Mailer’s novel “Executioner’s Song” Gary Gilmore, who enters the world of crime due to lack of love and constant nervousness in his childhood. As a teenager, Gary began to be engaged in petty crimes, going out on the streets to escape from the ongoing terrors and moral abuse in his family. Naturally, a child who did not feel light and love in his family could not show love, empathy to the people around him. As a result he always felt pain committing various crimes. Incredibly, Gilmore scored 133 at an IQ test, moreover, scored high marks both at aptitude and achievement tests. Nevertheless, unfortunate he dropped out of high school in the 9th grade despite his artistic and intellectual talent
Keywords: documentary novel,; family; crime; childhood